Rehabilitacija bolnikov po prebolelem sindromu Guillain-Barré - Šmid, Sonja (Rehabilitacija (Ljubljana), 2014)
Background: Guillain-Barré syndrome (GBS) is an acute inflammatory demyelinating polyradiculopathy that can cause severe impairments of many body structures and functions with consequent activities and participation limitations. The aim of our study was to assess rehabilitation outcome in these patients. Methods: Forty-five patients (20 women, 25 men) with Guillain- Barre syndrome who had completed primary rehabilitation between 2008 and 2011 at the University Rehabilitation Institute in Ljubljana were included in this retrospective study. We collected data on age, gender, duration of the rehabilitation and time from occurrence of the first symptoms of the disease to admission to inpatient rehabilitation. Manual muscle testing was used for assessment of limb function. Activities and participation were assessed using the Functional Independence Measure (FIM) and two walking tests (6-minute and 10-metre). Assessment was performed at admission and at discharge. Results: The mean age at admission was 58 years. On average, patients were admitted to inpatient rehabilitation 63 days (range from 20 to 210 days) after occurrence of the first symptom of the disease. The duration of rehabilitation was approximately 7 weeks. Regarding all observed variables, clinically important and statistically significant improvements were achieved (p < 0.001). At admission and at discharge medium to high statistically significant correlations between all the measures were observed (p < 0.01). Patients with a higher FIM score and better muscle strength were walking faster and walked a longer distance during the 6-minute walking test. Conclusion: Multidisciplinary care for GBS patients is effective. During relatively short inpatient rehabilitation, clinically important and statistically significant improvements regarding body functions, activities and participations are achieved.
Keywords: akutna poliradikulopatija; Functional Independence Measure; Guillain-Barre Syndrome; Lestvica funkcijske neodvisnosti; manual muscle testing; Polyradiculopathy; ročni mišični status; sindrom Guillain-Barré; testi hoje; walking test